A ‘wind of change’ that transformed the continent - United Nations (Africa Renewal, 2010)
When UK Prime Minister Harold Macmillan addressed the whitesonly South African parliament in February 1960, he could not have known that his speech would still be studied by historians years later. But that was the year 17 African countries achieved their independence, with many others soon to follow. His words were prophetic: “The wind of change is blowing through this continent, and whether we like it or not, this growth of national consciousness is a political fact. We must all accept it as a fact, and our national policies must take account of it.” Those remarks would come to be seen as the epitaph of European colonialism in Africa and the harbinger of an African nationalism sweeping irresistibly from the north.